South Africa: A Diceyan Rechtsstaat? - Venter, Francois (McGill Law Journal / Revue de droit de McGill, 2012)
South Africa’s transformation to constitutionalism in 1994 saw the addition to a mixed legal system of a supreme constitution that requires all law to conform to its provisions, principles, and values. This new constitutional design was developed for the circumstances and modeled on existing liberal democratic constitutions, the most influential of which were Canadian and German.Adopted in 1993, the first constitution introduced the notion of the “constitutional state” but being only a transitional document, it provided for the creation of a “final” constitution crafted in conformity with prescribed principles. The final constitution, adopted in 1996, made no mention of the “constitutional state”, including instead the expression “rule of law”. Since the constitutional principles laid down in 1993 referred to neither the German “Rechtsstaat”, nor Diceyan “rule of law”, the replacement of the former term by the latter was permissible.The two constitutional texts did not, however, elaborate on these two terms. It was left to constitutional interpreters, especially the judiciary, to give meaning to these historically disconnected but conceptually related ideas. The result was a completely novel and pervasive constitutional doctrine. The judicial process of merging these notions may be described as “comparison by global assimilation”.